Beliefs and attitudes about deprescription in older HIV-infected patients: ICARD Project - Giménez, Reyes Serrano (Rev Esp Quimioter, 2020)
OBJECTIVES: HIV population is aging at an earlier age than those uninfected, requiring more non-HIV medications to treat noncommunicable diseases. In the context of chronic HIV infection, the next therapeutic change would be the polymedication control. This paper has the purpose of explore the attitudes of older people living with HIV toward deprescribing. MATERIAL AND METHODS: This was an observational, prospective and multicenter study conducted from March-April, 2018. People living with HIV (PLWH) on highly active antiretroviral therapy and older than 65 years were included. In addition to demographic and pharmacotherapeutic data, attitudes regarding deprescribing were collected through the “Revised Patients’ Attitudes Towards Deprescribing Questionnaire”. RESULTS: A total of 42 patients were included in this study. Regarding their attitudes in relation to deprescription, there were three statements with the most consensuses. The first (“I have a good understanding of the reasons I was prescribed each of my medicines”) had 91.9% consensus. The second and third questions showed 89.2% consensus in both cases; “Overall, I am satisfied with my current medicines” and “I like to be involved in making decisions about my medicines with my doctors”. CONCLUSIONS: This study is the first to explore the beliefs and attitudes of older PLWH in relation to deprescription process. There are positive attitudes regarding medication knowledge but there also is a percentage of patients who had a negative opinion regarding deprescription. We must study and go deeper in our knowledge of techniques that could help us to better understand their preferences, in order to establish effective and successful deprescription strategies.